Acknowledgement for Reviewers in 2016 - Forum Geografi, Editors (Universitas Muhammadiyah Surakarta, 2016)
The editors of Forum Geografi would like to express their sincere gratitude to the following reviewers for assessing manuscripts in Volume 30 2016.Â Prof. Dr. Junun Sartohadi, Universitas Gadjah Mada, IndonesiaProf. Dr. Ir. Hidayat Pawitan, Department of Geophysics and Meteorology, Bogor Agricultural University, IndonesiaDr Muhammad Kamal, UGM, IndonesiaSupari, BMKG Indonesia, Indonesia; Universiti Kebangsaan Malaysia, School of Environmental and Natural Resource Sciences, Bangi, MalaysiaMuhammad Haikal Karana Sitepu, University of Leeds, United KingdomDr. Yanto,Â Civil, Universitas Jenderal Soedirman, IndonesiaÂ R Muhammad Amin Sunarhadi, Universitas Muhammadiyah SurakartaDr. Sukamdi, IndonesiaDr. Peter Oberle, Institute for Water and River Basin Management (IWG)Karlsruhe Institute for Technology (KIT)KarlsruheGermany, GermanyProf. Dr. Muhammad Aris Marfai, Universitas Gadjah MadaDr. Pramaditya Wicaksono, Cartography and Remote Sensing Dept. of Geographic Information Science Faculty of Geography Universitas Gadjah Mada, IndonesiaDr. Sushil K. Joshi, Indian Institute of Remote Sensing (India), IndiaDr. Djati Mardiatno, UGM, IndonesiaDr. Purnama Budi Santosa, Gadjah Mada University, IndonesiaDr. Donaldi S. Permana, Center for Research and Development Indonesian Agency for Meteorology Climatology and Geophysics (BMKG); Byrd Polar and Climate Research Center and School of Earth Sciences, Ohio State University, Columbus, Ohio, USA, IndonesiaA Cipta, Geological Agency of Indonesia, Jalan Diponegoro No. 57, Bandung 40122, Indonesia Australian National University, Research School of Earth Sciences, Building 142, Mills Road, Canberra, ACT 0200, Australia, AustraliaDr Takanori Horii, Research and Development Center for Global Change (RCGC), Strategic Research and Development Area, Japan Agency for Marine-Earth Science and Technology (JAMSTEC), Yokosuka, Kanagawa, Japan, JapanHari Agung Adrianto, Institute Pertanian Bogor, IndonesiaDr. Adriana GarcÃa-Rama, Department of Land, Environment, Agriculture and Forestry, University of Padova, Italy, ItalyDr. Kuswaji Dwi Priyono, Fak Geografi UMS, IndonesiaDr. Rini Rachmawati, Faculty of Geography, Universitas Gajah Mada, IndonesiaDr. Dyah R HisbaronÂ ,Faculty of Geography,Â Universitas Gajah MadaDr. Saut Sagala, Intitut Teknologi Bandung, IndonesiaÂ We greatly appreciate the contribution of expert reviewer, which is crucial to the journalâs editorial decision-making process and to the quality of the work that we publish.Â Â